Highly abundant pea LTR retrotransposon Ogre is constitutively transcribed and partially spliced - Neumann, Pavel; Pozárková, Dana; Macas, Jirí (Plant molecular biology, 2003)
We have isolated and characterized a novel giant retroelement, named Ogre, which is over 22 kb long and makes up at least 5% of the pea (Pisum sativum L.) genome. This element can be classified as a Ty3/gypsy-like LTR retrotransposon based on the presence of long terminal repeats (LTRs) and the order of the domains coding for typical retrotransposon proteins. In addition to its extreme length, it has several features which make it unique among the retroelements described so far: (1) the sequences coding for gag and prot proteins are separated from the rt/rh-int domains by several stop codons; (2) the region containing these stop codons is removed from the element transcripts by splicing which results in reconstitution of the complete gag-pol coding sequence; (3) only a part of the transcripts is spliced which probably determines the ratio of translated proteins; (4) the element contains an extra ORF located upstream the gag-pol coding sequences, potentially coding for a protein of 546-562 amino acids with unknown function. The transcriptional activity of the Ogre elements has been detected in all organs tested (leaves, roots, flowers) as well as in wounded leaves and protoplasts. Considering this retroelement's constitutive expression and observed high mutual similarity of the element genomic sequences, it is possible to speculate about its recent amplification in the genomes of pea and other legume plants.
Keywords: sekvence nukleotidů; Sequence Homology, Nucleic Acid; Genome, Plant; genom rostlinný; Sequence Analysis, DNA; Transcription, Genetic; sekvenční analýza DNA; molekulární sekvence - údaje; sekvenční homologie nukleových kyselin; sekvenční seřazení; retroelementy; Fabaceae; regulace genové exprese u rostlin; Retroelements; DNA rostlinná; genetická transkripce; Pisum sativum; DNA, Plant; alternativní sestřih; otevřené čtecí rámce; Gene Expression Regulation, Plant; Open Reading Frames; hrách setý; Molecular Sequence Data; Alternative Splicing; Base Sequence; Sequence Alignment